Quelques Diptères Dolichopodides (Deuxième article). - Parent, Octave (Beiträge zur Entomologie = Contributions to Entomology, 1954)
Nomenklatorische Handlungen flavizonatus Parent, 1954 (Condylostylus), spec. n. vaalensis Parent, 1954 (Hydrophorus), spec. n. bicolor Parent, 1954 (Nematoproctus), spec. n. apicalis Parent, 1954 (Paraclius), spec. n. bidilatata Parent, 1954 (Porphyrops), spec. n. peregrinus Parent, 1954 (Syntormon), spec. n. anale Parent, 1954 (Syntormoneurum), spec. n.